Patient engagement in radiation oncology: a large retrospective study of survey response dynamics - Loving, Bailey A.; Ye, Hong; Rutka, Elizabeth; Robertson, John M. (Frontiers in Oncology, 2025)
PurposePatient satisfaction surveys are pivotal in evaluating healthcare quality and enhancing patient care. Understanding the factors influencing patient engagement with these surveys in radiation oncology can guide improvements in patient-centered care.MethodsThis retrospective study analyzed data from radiation oncology patients at a large multi-site single-institution center from May 2021 to January 2024. We assessed the influence of demographic, clinical, and socioeconomic factors on the likelihood of survey participation using univariate (UVA) and multivariable (MVA) logistic regression analyses. Factors included age, gender, race, socioeconomic status (SES) via Area Deprivation Index (ADI), language, marital status, smoking, employment, insurance type, mental health disorders (MHD), comorbidity index (CCI), and cancer type.ResultsIn a comprehensive analysis of 11,859 patients, most were female (57.2%), over 65 years old (60.7%), and primarily insured by Medicare (45.9%). MVA showed that higher socioeconomic disadvantage significantly decreased survey participation (ADI third tertile vs. first tertile OR=0.708, p<0.001), with each unit increase in ADI reducing the odds of completion by 1% (p<0.001). Older adults, and patients with head and neck or genitourinary cancers were significantly more likely to participate, while those with higher comorbidities, MHD, or other minority status were less engaged (p<0.001). Telemedicine encounters also significantly increased participation compared to in-person visits (OR=1.149, p=0.006).ConclusionsMultiple factors including age, race, SES, insurance type, cancer type, health conditions, and modality of healthcare delivery influence patient engagement with satisfaction surveys in radiation oncology. Strategies to enhance patient engagement must consider these diverse influences to ensure comprehensive and inclusive feedback mechanisms in healthcare settings. Tailored interventions to mitigate barriers specific to underrepresented groups are crucial for capturing a broad spectrum of patient experiences and improving the overall quality of patient care.